Refractory angiolymphoid hyperplasia with eosinophilia: Complete resolution with low dose thalidomide. Issue 6 (9th June 2022) - Khurana, Ananta; Savitha, B
Abstract: Angiolymphoid hyperplasia with eosinophilia (ALHE) is a difficult‐to‐treat and rare benign vascular proliferative condition which presents as painless, solitary, or multiple vascular papules or nodules in the head and neck area, with predilection for the ear. We report a case of ALHE that failed multiple therapeutic interventions but achieved complete resolution when treated with thalidomide.